Optimal sizing of TCSC using ant colony optimization (ACO) technique for loss minimization: article - Abdullah, Mukhtaruddin; Musirin, Ismail (Universiti Teknologi MARA (UiTM), 2008)
This paper present finds optimal location of Thyristor Controlled Series Capacitor (TCSC) using Ant Colony Optimization (ACO) technique in loss power minimization at transmission line (used 57 bus system). Recent year, TCSC has been increasingly installed in transmission line system in many part of the world. The installation based on the location and size of the capacitor. Power transmission loss of grid can be improve be improved by upgrading or adding of new transmission circuit TCSC offer a strong alternative for optimizing of transmission over power link, existing as well as new, by means intended for the control of power flow, improvement of stability, voltage profile management, power factor correction, and power losses. The optimal TCSC placement has been implemented by using MA TLAB programming.